OPTIMALISASI PELAYANAN BAGIAN TELLER DENGAN METODE ANTRIAN PADA GERAI SAMSAT NUSA DUA - Riski, I Putu; Setiawan, Putu Yudi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p05, 2024)
One-Stop Single Administration System (SAMSAT) is a government program that aims to serve the public in the process of paying vehicle tax. Queuing is a process formed when the arrival of customers exceeds the number of facilities serving it, so that when a system experiences congestion it is said to contain a queue. This study aims to determine the optimal service conditions and queuing system at Nusa Dua SAMSAT outlets, Jl. Bypass Nusa Dua, Badung, Bali. The number of samples taken was 55 respondents selected using the accidental sampling method which is seen as a source of research data. The results of the study show the queuing type model used by the Nusa Dua SAMSAT outlets is a Single Channel - Multi Phase queue type. Futhermore, the result of analysis also shows that the pattern of service to taxpayers is not exponentially distributed with a value of 0.000 and the pattern of arrival of taxpayers is a Poisson distribution with a value of 0.433. The total number of arrivals of taxpayers per unit of time (? (is 7 customers/hour and the average total value of the number of taxpayers served per unit of time (µ) is 3 customers/hour and the calculation of 5 service servers. From the results of this study it is known that the performance of tellers at the SAMSAT Nusa Dua outlet is not optimal.